2016
DOI: 10.1016/j.scitotenv.2016.04.152
|View full text |Cite
|
Sign up to set email alerts
|

Development of a conceptual framework of holistic risk assessment — Landfill as a particular type of contaminated land

Abstract: Landfills can be regarded as a particular type of contaminated land that has a potential to directly and indirectly pollute all of the four main spheres of the environment which are the lithosphere, atmosphere, hydrosphere and eventually adversely impact the biosphere. Therefore, environmental risk assessment of a landfill has to be more integrated and holistic by virtue of its nature of being a multidimensional pollutant source. Despite this, although various risk assessment approaches have been adopted for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Bjerg et al, 2011;Butt et al, 2008). Butt et al (2016) presented a conceptual framework for a holistic risk assessment of landfills. The fundamental and initial stage of any risk assessment is the baseline study including geology, hydrology, hydrogeology, topography, meteorology, geography, human influences and site management (Butt et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Bjerg et al, 2011;Butt et al, 2008). Butt et al (2016) presented a conceptual framework for a holistic risk assessment of landfills. The fundamental and initial stage of any risk assessment is the baseline study including geology, hydrology, hydrogeology, topography, meteorology, geography, human influences and site management (Butt et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the role of water in the circulation of chemical components between different elements of the environment, the analysis covered also the contamination of water with trace elements, in particular with heavy metals. Metals in groundwater can occur due to penetration of pesticides and mineral fertilizers used in crop fields, but can also get from leachates from landfills and from industrial and municipal wastewater [16][17]19]. The concentration of heavy metals in groundwater near the industrial waste landfill in Zgierz is shown in Figures 6-9.…”
Section: Resultsmentioning
confidence: 99%
“…The scope of the monitoring was specified by numerous regulations defining its area as well as method and frequency. All these efforts are aimed at protecting the environment and, consequently, human health [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…This was due to the fact that the variables related to this parameter commonly trigger severe damage to humans and the environment within the watersheds. Such affectations are described in detail in Araiza [46] and Butt et al [60]. They are even often referred to as risks associated with MSW management.…”
Section: Comments About Parameter and Variable Weightsmentioning
confidence: 99%